Should My Patient with Inflammatory Bowel Disease on Immunosuppressive Therapy be Vaccinated against Influenza Virus? - Neeraj Narula; Deborah LR Yamamura; John K Marshall (Canadian Journal of Gastroenterology)
Crohn’s disease and ulcerative colitis are variants of inflammatory bowel disease (IBD) for which immunosuppressive therapy is often required. Immunosuppressed patients are at increased risk for infections, including vaccine-preventable diseases such as influenza. Although several guidelines recommend routine influenza immunization for such patients, recent literature suggests that this patient population may be inadequately immunized. Current research suggests that inactivated influenza vaccines are effective, well tolerated and can be administered safely in most IBD patients. Studies in other immunosuppressed populations have also demonstrated the safety of inactivated vaccines. The present article reviews the literature regarding the safety and efficacy of influenza vaccination in IBD patients receiving immunosuppressive therapy.